TRADITIONAL MARKET TRADERS' PERCEPTION OF ONLINE SALES IN INCREASING INCOME IN THE PANDEMI ERA (Medan MMTC Market Case Study) - Ketry Setya Wardani; Hastina Febriaty (Proceeding International Seminar of Islamic Studies, 2021)
In this era of all-technology, especially during the current Covid-19 Pandemic, people should have adapted so that they can survive difficult times due to limited activities due to the influence of social restrictions as a result of the pandemic. Traditional markets are one of those affected by the pandemic, where traders admit that they have difficulty selling their wares because the number of buyers coming has decreased since the government asked residents to reduce activities outside the home. The topic raised in this research is based on the phenomenon that occurs with the reduced income of traditional market traders, are traders interested in joining the marketplace to increase their income. The main objective of this research is to conduct an analysis to find out the perceptions of MMTC traditional market traders towards the marketplace in increasing income during a pandemic. The data used is primary data that is sourced from questionnaires with descriptive analysis techniques. Based on the research results, it is known that traditional market traders in the MMTC market want to join the marketplace because they believe that joining the marketplace is to increase income, maintain business during a pandemic, provide convenience, and become a safe shopping solution during the Covid-19 pandemic.